PLACE AND ROLE OF NON-ACADEMIC EDUCATION IN THE SUBJECT FIELD OF PHILOSOPHY OF EDUCATION - Galyna Zhukova ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
Growing problem of inconsistency of the academic system of education with the new needs of society and individual, lack of existing structures of education contribute to the emergence of a different approach for the organization of educational activities, which is non academic. As a philosophical phenomenon, it fully complies with the students' diverse interests and possibilities. Nonacademic education functions outside the academic education, free from strict rules and regulations, it focuses on specific educational requests of different social, professional, demographic groups.